BAUSUNG DALAM PENGANTIN MENURUT HUKUM ISLAM - M. Fikri Nurdiandi (CV. Adiba Aisha Amira, 2022)
The author's research is to discover the customs and traditions of the Banjari people in the wedding procession. Customs and traditions related to wedding processions have been practiced by the indigenous Banjars since ancient times from the ancestors of the Banjar tribe. The procession before the Walimahan wedding has a sequence that must be carried out by the bride and groom, starting from Basasuluh, Batatakunan, Badang, Maantar Patalian, Maantar and so on until reaching the Walimatul Ursy stage. The purpose of this study is to find out the implementation of the banjar traditional wedding ceremony tradition in the Banjar community, knowing the importance of wedding traditions in banjar traditional wedding ceremonies. Some traditional scholars and scholars about the tradition of marriage in traditional weddings in Banjar. This research is a field research with an empirical legal approach to qualitative research methods. The data type and source are primary data and secondary data. Observations and interviews are used as data collection instruments. The result of this study is that, first, the implementation of the Bausung tradition has an implied meaning, namely respect for ancestors, maintaining culture and avoiding all unwanted things. Second, the banjar customary marriage process is allowed in terms of Islamic law, it's just that it needs to be restructured to be in accordance with Islamic law, namely. It is believed (aqidah) and also there should be a change of the person who wears it for women, it must be mahram